Pembelajaran Text Preprocessing berbasis Simulator Untuk Mata Kuliah Information Retrieval - Hermawan, Latius; Bellaniar Ismiati, Maria (Jurnal Transformatika, 2020)
Preprocessing is an important task and step in Information Retrieval. Information Retrieval (IR) is used to decide which documents in a collection must be taken to meet the user's information needs. The comparison is done in 4 steps in preprocessing, namely Case folding, Tokenizing, Filtering, Stemming.All stages of the preprocessing are done manually during the teaching-learning process. The lecturer explained by writing and explaining one by one the correct words at each stage and students also manually reviewed each stage. Simulator is needed to help solve existing problems. The simulator has been successfully created by displaying 6 menus. The simulator has succeeded in outputting each stage according to the manual theory. From the results of the testing questionnaire,> 90% of respondents thought that using this simulator made it easier to work on the four stages of text pre-processing so that the time needed also became efficient.